The Influence Of Halal Literacy and Religiosity on the Interest in Consuming Halal Food in Surabaya City - Syifa', Siti Robi'atus; Suryaningsih, Sri Abidah (ASEAN Journal of Halal Study, 2024)
In Islam, it is required to eat halal and thoyyib food, but this is still not understood by some people. Until now, some people have not seen the impact of religious understanding on halal products. This study aims to analyze the influence of halal literacy and religiosity on halal food consumption interest among Surabaya city residents. This research uses a quantitative approach with prime data by distributing questionnaires to respondents via Google Form and then processing them using SPSS statistical tools. The results of this study show that the variables of halal literacy and religiosity partially and simultaneously affect the interest in consumption of halal food in the city of Surabaya, with a contribution value of 65.9%.